Exploring the Influence of the Community-Based Sports Club Environment on the Support and Development of Volunteer Women Coaches in Ireland - Irene Hogan; Richard Bowles; Niamh Kitching (Frontiers Media S.A., 2022)
In Ireland, the majority of coaches at non-elite level are volunteers and within the female-only team sport of women's Gaelic football, most qualified coaches are women. Yet, little is known on the club specific experiences of volunteer women coaches in non-elite sport. To address this gap, 11 women coaches, from three Gaelic Football clubs, were interviewed to explore the influence of the community-based club environment on their support and development in the role. The participants were actively coaching and part of a Community of Practice (CoP) focusing on developing their club's coaching structures. A creative non-fiction approach combined the key themes from the 11 interviews into three coach profiles of a novice coach, experienced coach, and a player-coach. Retention and recruitment, support structures within the club, and club culture and norms were the key themes identified. This study recommends that clubs employ support structures that support and develop volunteer women coaches and address any behavior in the club that negatively impacts on their role.